Dendritic Ca(2+) signalling due to activation of α7-containing nicotinic acetylcholine receptors in rat hippocampal neurons - Fayuk, Dmitriy (Blackwell Science Inc, 2007)
Neuronal nicotinic acetylcholine receptors (nAChRs) are in the superfamily of Cys-loop ligand-gated ion channels, which are widely expressed in the brain. Among the many different subtypes of nAChRs known to be expressed in the rat brain, the α7-containing nAChRs are considered to be the most permeable to Ca(2+). Utilizing highly localized and rapid iontophoretic agonist delivery, combined with patch-clamp electrophysiology and fura-2 fluorescence imaging techniques, we examined the α7 nAChR-mediated currents and [Ca(2+)](i) transients in the dendrites of rat hippocampal CA1 interneurons in the slice. We found that in the dendrites, whereas the amplitudes of the current responses were smaller and the decay kinetics faster than the responses in the soma, the amplitudes of the [Ca(2+)](i) signals were significantly larger. Cultured hippocampal neurons were studied since the dendritic field lies in the same focal plane, which allowed for a broader investigation of the spatiotemporal dynamics of [Ca(2+)](i) signalling. In cultured neurons, the [Ca(2+)](i) signals in the dendrites were similar to those in slices. Interestingly in cultures, even though the amplitude of the α7 nAChR-mediated currents dramatically decreased with distance from the soma (from ∼20–250 μm), the amplitude of the [Ca(2+)](i) signals did not correlate with distance. This indicates that the relative efficacy of α7 nAChR activation to increase [Ca(2+)](i) levels in dendrites increased severalfold with distance from the soma. These results may have implications for the role that α7 nAChRs have in regulating various signal transduction cascades, synaptic plasticity, and memory processes, via significant changes in [Ca(2+)](i) levels.